The Private Side of a New Security Identity in French Cities - Bauvet, Sébastien (Political Preferences, 2018)
Focusing on the joint analysis of security trends and the organization of the private security market in France, this article addresses the new relationships between different security players and modern citizenship and society within the framework of metropolization. Despite the construction of an extended sovereign power, especially after the Second World War, the governments started to cooperate in the 1990s with other partners and to vary the levels of decision making in terms of security policies. Experts from private security companies or local councillors are new operators in the so-called “security co-production”. An analysis at the metropolis scale seems important in order to understand the issues related to security for two reasons: firstly, because of the particular pressure connected to the recent terrorist attacks than can affect the “identity” of the city; secondly, because “incivility” – constructed as a major political problem since the 1990s – is linked to social structures of local territories within a wider one, with differentiated means for the people who live in the metropolitan center of social framework. The social representations of order and social control are still based on the relationships between private property, transports and public (access) spaces. The new security identity of cities depends on the relationships between local policies and the socio-economic reality of citizens, including private security guards, whose life conditions are an expression of the paradoxes of modern life. Key words: private security, professionalization, metropolis, social control